Le pluralisme politique de l’Ouest canadien - Florence Cartigny (Anglophonia)
Regionalism has played a tremendous part in defining Canadian identity in a federation still divided along regional lines. Since the 1870s, Western Canada has often felt left aside from the politically powerful provinces of Ontario and Quebec: this federal lack of interest goes hand in hand with unfair representative power both in the Senate and in the House of Commons.As a result, this politically and economically divergent region has created several political parties. For example, the CCF originated in Western Canada in the 1930s with strong socialist leanings. During the Great Depression, William Aberhart founded the Social Credit which had a long-term influence in Alberta. As for the Reform Party, whose only leader was Preston Manning, it remained a federal party whose original aim was to promote Western issues in Ottawa. Finally, separatist parties came into being with the involvement of Douglas Christie at the head of the Western Block Party.Undoubtedly, Westerners have shown how dynamic involved they could be to see their diversity represented provincially and federally. And yet, political heterogeneity is not always reflected: indeed, it seems that Western Canada is heading from a two-party system to a one-party system where political organizations have different labels or names rather than deep ideological divergences